Temporal trends in management and outcome of diabetic and non-diabetic patients with acute coronary syndrome (ACS): Residual risk of long-term mortality persists: Insights from the ACS Israeli Survey (ACSIS) 2000–2010. (20th January 2015) - Klempfner, Robert; Elis, Avishay; Matezky, Shlomi; Keren, Gad; Roth, Arie; Finkelstein, Ariel; Banai, Shmuel; Goldenberg, Ilan; Fisman, Enrique Z.; Tenenbaum, Alexander; Arbel, Yaron
Abstract: Background/Objectives: In the past diabetes was strongly associated with elevated mortality rate after acute coronary syndrome (ACS). Over the past decade a treatment of the ACS has evolved rapidly with major advances in the management techniques. The aim of the present study was to compare temporal trends of the outcomes of diabetic vs. non-diabetic patients using nationwide data. Methods: We evaluated time-dependent changes in the clinical characteristics, management strategies, and outcomes of diabetic and non-diabetic patients enrolled in the biannual ACS Israeli Surveys (ACSIS) between 2000 and 2010. We divided the survey into early (2000–2005) vs. late (2006–2010) periods. Results: There were 3964 diabetic and 7322 non-diabetic patients, a total of 11, 472 ACS patients. Although diabetic patients were significantly younger, they displayed more advanced coronary artery disease and considerably higher rates of all-cause mortality at 30 days and 1-year. Both diabetic and non-diabetic patients who were enrolled in the late survey period received more evidence-based therapies (primary PCI, guideline-based medications) and experienced a better 1-year survival probability (respectively 88% vs. 84% and 93% vs. 90%; all p-values < 0.01). Multivariate analysis demonstrated that diabetes and early survey period were each independently associated with a significantly increased mortality risk (respectively 39% and 25%, p < 0.001 for both). Conclusion: Our data suggest that despite the overall improvement in the management and outcomes of the ACS, diabetic patients are still at increased residual risk of long-term mortality that needs to be further addressed.